Pengaruh Parenting Stress terhadap Harga Diri Orangtua di JABODETABEK - Lita Patricia Lunanta; Andi Rina Hatta; Veronica Kristiyani; Srifianti Srifianti (MANASA, 2021)
Situations that parents handle affect how they parent their children and this will affect howtheir children develop later on. The aim of this research is to analyze how parenting stressaffects other factors in parent’s psychological condition, especially in their self-esteem. Thisresearch was held to parents with middle school children who live in JABODETABEK with241 participants. The scale that was used to measure parenting stress is the one that Berry andJones (1995) developed and to measure self-esteem is The Coopersmith Self-Esteem Inventorythat was developed by Ryden (1978). This research used a quantitative descriptive method todescribe parenting stress and self-esteem of participants and used simple regression analysisto measure how parenting stress affects self-esteem of middle school children’s parents. Fromthe statistical analysis it was found that parenting stress contributed negatively (t (241) = -7.330, p <0.005) to self-esteem of parents with middle school age children in JABODETABEK.The higher the parenting stress the lower self-esteem becomes. Parenting stress contributed 18percent to self-esteem that means the remaining 82 percent of a parent's self-esteem wasdetermined by other factors.